Testosterone administration inhibits hepcidin transcription and is associated with increased iron incorporation into red blood cells - Guo, Wen; Muckenthaler, Martina (Aging cell, 2013)
Testosterone administration increases hemoglobin levels and has been used to treat anemia of chronic disease. Erythrocytosis is the most frequent adverse event associated with testosterone therapy of hypogonadal men, especially older men. However, the mechanisms by which testosterone increases hemoglobin remain unknown. Testosterone administration in male and female mice was associated with a greater increase in hemoglobin and hematocrit, reticulocyte count, reticulocyte hemoglobin concentration, and serum iron and transferrin saturation than placebo. Testosterone downregulated hepatic hepcidin mRNA expression, upregulated renal erythropoietin mRNA expression, and increased erythropoietin levels. Testosterone-induced suppression of hepcidin expression was independent of its effects on erythropoietin or hypoxia-sensing mechanisms. Transgenic mice with liver-specific constitutive hepcidin over-expression failed to exhibit the expected increase in hemoglobin in response to testosterone administration. Testosterone upregulated splenic ferroportin expression and reduced iron retention in spleen. After intravenous administration of transferrin-bound 58Fe, the amount of 58Fe incorporated into red blood cells was significantly greater in testosterone-treated mice than in placebo-treated mice. Serum from testosterone-treated mice stimulated hemoglobin synthesis in K562 erythroleukemia cells more than that from vehicle-treated mice. Testosterone administration promoted the association of androgen receptor (AR) with Smad1 and Smad4 to reduce their binding to bone morphogenetic protein (BMP)-response elements in hepcidin promoter in the liver. Ectopic expression of AR in hepatocytes suppressed hepcidin transcription; this effect was blocked dose-dependently by AR antagonist flutamide. Testosterone did not affect hepcidin mRNA stability. In conclusion, testosterone inhibits hepcidin transcription through its interaction with BMP/Smad signaling. Testosterone administration is associated with increased iron incorporation into red blood cells.
Gesehen am 01.02.2021